The Neutrons for Science Facility at SPIRAL-2. Issue 1 (21st November 2017) - Ledoux, X; Aïche, M; Avrigeanu, M; Avrigeanu, V; Balanzat, E; Ban-d'Etat, B; Ban, G; Bauge, E; Bélier, G; Bém, P; Borcea, C; Caillaud, T; et al.
Abstract: The neutrons for science (NFS) facility is a component of SPIRAL-2, the new superconducting linear accelerator built at GANIL in Caen (France). The proton and deuteron beams delivered by the accelerator will allow producing intense neutron fields in the 100 keV–40 MeV energy range. Continuous and quasi-mono-kinetic energy spectra, respectively, will be available at NFS, produced by the interaction of a deuteron beam on a thick Be converter and by the 7 Li(p, n) reaction on thin converter. The pulsed neutron beam, with a flux up to two orders of magnitude higher than those of other existing time-of-flight facilities, will open new opportunities of experiments in fundamental research as well as in nuclear data measurements. In addition to the neutron beam, irradiation stations for neutron-, proton- and deuteron-induced reactions will be available for cross-sections measurements and for the irradiation of electronic devices or biological cells. NFS, whose first experiment is foreseen in 2018, will be a very powerful tool for physics, fundamental research as well as applications like the transmutation of nuclear waste, design of future fission and fusion reactors, nuclear medicine or test and development of new detectors.